2001
DOI: 10.1002/1520-6378(200104)26:2<141::aid-col1005>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five sets of color difference data

Abstract: In a systematic optimization process five sets of recent color difference data have been analyzed for commonalities. Adjustment of the X tristimulus values and application of a systematic, surround dependent S L function was found to be beneficial in all cases. Other modifications of the CIE94 color-difference formula were found to bring improvements only in some cases and may be spurious. Application of what seem to be nonsystematic scale factors in a range of 0.78 -1.38 improve correlation between calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Unfortunately, the issue of how to account for sample separation when deriving visual thresholds of color differ-ences is still not resolved. 37 In the past, several studies have been published on this issue, but no consensus was reached. One common result of the studies that has been published, however, is that the presence of a gap generally leads to less tight color tolerances.…”
Section: The Gap Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the issue of how to account for sample separation when deriving visual thresholds of color differ-ences is still not resolved. 37 In the past, several studies have been published on this issue, but no consensus was reached. One common result of the studies that has been published, however, is that the presence of a gap generally leads to less tight color tolerances.…”
Section: The Gap Effectmentioning
confidence: 99%
“…Unfortunately, the issue of how to account for sample separation when deriving visual thresholds of color differences is still not resolved . In the past, several studies have been published on this issue, but no consensus was reached.…”
Section: Some Current Issues In Setting Qc Color Tolerancesmentioning
confidence: 99%
“…Textile samples, typically compared juxtaposed, exhibit a moderate level of lightness crispening. The effect has recently been described quantitatively for colour difference data by Lübbe [23] and Kuehni [24] but has not yet become a component of commonly used colour difference formulas despite the fact that there is no effective local or global industry standardisation of viewing surround conditions.…”
Section: Lightness Contrastmentioning
confidence: 99%
“…Since the late 1980s, visual experiments have been performed to develop different suprathreshold color-difference datasets to be used for improving the relationship between visual and numerical color difference evaluation [1][2][3][4][5][6] . Based on the results of these experiments several datasets have been developed such as: the CMC dataset (MacDonald, 1984), the BFD dataset (Luo et Rigg, 1987), the RIT-DuPont dataset (Berns, 1991), the LCD dataset (Kim et Nobbs, 1997) and the Witt dataset (Witt, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies showed that LCD and CRT display can be used for virtual proofing and that they can be accurately colorimetrically characterized. 6,11 Our experimental tests were done under illuminating/viewing conditions close to the ''reference conditions'' suggested for the CIEDE2000 color-difference formula (CIE Publication 142-2001) and by the ISO standard 3668:2003 (ISO standard 3668:2003 Paints and varnishesVisual comparison of the colour of paints). In our study we controlled viewing conditions including the spectral power distribution of the viewing environment and the spectral reflectance factors of surface specimens.…”
Section: Introductionmentioning
confidence: 99%